Community and caregiver perceptions of giving care to seniors. (September 2019) - Waniger, Anne; Gale, Kathy; DeNomie, Melissa; Nelson, David
Background: Family caregivers of seniors and disabled adults frequently bear the responsibility of aiding in instrumental activities of daily living and locating resources, often while raising their own families. As the demand for care rises, caregivers may experience declining physical health and increased social and emotional stress compared to their noncaregiving counterparts. This study aims to better understand the journey of unpaid family caregivers and identify opportunities for improvement across organizations, policies, systems, and teams. Research design and methods: A purposive sample of 28 current and former unpaid caregivers of seniors or people with disabilities (26 females and 2 males) participated in four separate focus groups. Recordings were transcribed verbatim and analyzed using open coding. Results: Six major themes surrounding the experience of caregiving emerged from the coding process: Ambivalence, "Boiling Point, " Coping, Acknowledgment and Acceptance, Family Dynamics, and Interaction with the System. Focus groups indicated an urgent need to identify and support unpaid caregivers earlier in their trajectory of caring for a senior and to provide consistent, right-time resources over the trajectory of the senior's lifespan. Discussion and implications: The rational, emotional, and relational components of caregiving represent distinct but overlapping themes within the experience of giving care. Each theme influences another, creating an experience that is complex, fluid, and sensitive to change. The system surrounding caregivers must proactively identify caregivers as equal members of the care team for a senior or disabled adult early in the patient's disease trajectory.